Extracorporeal membrane oxygenation in spina bifida and (H1N1)-induced acute respiratory distress syndrome - Jansen, Oliver (J Artif Organs, 2017)
Acute respiratory distress syndrome (ARDS) is characterized as an acute hypoxemic and/or hypercapnic respiratory failure seen in critically ill patients and is still, although decreased over the past few years, associated with high mortality. Furthermore, ARDS may be a life-threatening complication of H1N1 pneumonia. We report on a 45-year-old spina bifida patient with confirmed H1N1 influenza virus infection causing acute respiratory failure, who was successfully weaned from 42-day veno-venous extracorporeal membrane oxygenation (vv-ECMO) treatment with an excellent outcome. Due to the physical constitution of spina bifida patients, we experienced challenges concerning cannula positioning and mechanical ventilation settings during weaning.